Free Recall of Bound Information Held in Short-Term Memory is Unimpaired by Age and Education. (17th April 2019) - Yassuda, Mônica Sanches; Carthery-Goulart, Maria Teresa; Cecchini, Mario Amore; Cassimiro, Luciana; Fernandes, Katarina Duarte; Baradel, Roberta Roque; Garcia, Ricardo Basso; Nitrini, Ricardo; Della Sala, Sergio; Parra, Mario Alfredo
Abstract: Objectives: It has been challenging to identify cognitive markers to differentiate healthy brain aging from neurodegeneration due to Alzheimer's disease (AD) that are not affected by age and education. The Short-Term Memory Binding (STMB) showed not to be affected by age or education when using the change detection paradigm. However, no previous study has tested the effect of age and education using the free recall paradigm of the STMB. Therefore, the objective of this study was to investigate age and education effects on the free recall version of the STMB test under different memory loads. Methods: 126 healthy volunteers completed the free recall STMB test. The sample was divided into five age bands and into five education bands for comparisons. The STMB test assessed free recall of two (or three) common objects and two (or three) primary colors presented as individual features (unbound) or integrated into unified objects (bound). Results: The binding condition and the larger set size generated lower free recall scores. Performance was lower in older and less educated participants. Critically, neither age nor education modified these effects when compared across experimental conditions (unbound v. bound features). Conclusions: Binding in short-term memory carries a cost in performance. Age and education do not affect such a binding cost within a memory recall paradigm. These findings suggest that this paradigm is a suitable cognitive marker to differentiate healthy brain aging from age-related disease such as AD.